Vandium dioxide active plasmonics - Ooi, Kelvin J. A. (2013)
The insulator-metal transition (IMT) property of vanadium dioxide provides a large, abrupt change in refractive index, making it a good candidate active material for optical modulators. We show, in this paper, that plasmonic modulators can leverage the high modulation contrast of vanadium dioxide, while at the same time solve the problems of high insertion loss and high phase-transition electric-field threshold faced by vanadium dioxide photonic modulators. Our simulation results show that vanadium dioxide plasmonic slot and hybrid-slot waveguide modulators can achieve extinction ratios in excess of 10dB/μm with insertion losses as low as 2dB/μm. We also show that vanadium dioxide can be used to build plasmonic ring modulators. These high performance modulators are foundations to realizing plasmonic nanocircuits for next-generation chip technology.